Relationship Between Chemical Component and In Vitro Digestibility of Tropical Grasses - PRAPTI MAHYUDDIN (HAYATI Journal of Biosciences, 2008)
Fifty samples of leaf and stem of Sorghum stipodeum, Themeda australis, Iseilema vaginiflorum, Brachyacne convergens, and Dicanthium fecundum with different stage of maturity were used to study the relationship between their chemical components and in vitro dry matter digestibility (IVDMD). The IVDMD was performed by two stage of digestion; the first stage was digestion in rumen inoculum and the second stage was digestion of protein using neutral detergent solution. The relationship between chemical components and IVDMD was analysed using regression method. There was a negative correlation between fiber component [neutral detergent fiber (NDF), acid detergent fiber (ADF), and lignin] and a positive correlation between water soluble extract (WSE) or crude protein with IVDMD. Water soluble extract was the best predictor of IVDMD with r = 0.71 and residual standard deviation of 8.4 unit. Since the method of WSE is simple and inexpensive, it can be used as a predictor of dry matter digestibility of most forages. Although there were large variation exist among the species, however, the stage of maturity was an important factor affecting IVDMD showed in four out of five species tested. In two of the five species measured, the IVDMD were higher in leaf than that in stem. Key words: in vitro dry matter digestibility (IVDMD), chemical component, forage quality, maturity